Photosensitive / thermosetting / developable resin composition, dry film thereof, cured product thereof, and printed wiring board formed using the same

By optimizing the combination of resin filler and additives, the cracking problem of printed circuit board pad registration agent under hot and cold impact is solved, the printing performance and hardness are improved, and the demand for high-reliability electronic materials is met.

JP2025503073AActive Publication Date: 2025-01-30TAIYO INK SUZHOU
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024543264
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-12-27
Publication Date
2025-01-30
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

The pad registration agent of existing printed circuit boards is prone to cracking under hot and cold impact, and the printing performance and hardness are insufficient, making it difficult to meet the needs of high-reliability electronic materials such as automobiles.

Method used

Using a specific proportion of resin fillers and additive combinations, including vinyl ester resins, photopolymerization initiators, phosphate dispersants and inorganic fillers (such as quartz and titanium dioxide), the filler ratio is optimized to improve hot and cold impact performance and printing performance.

Benefits of technology

It realizes high impact resistance and good printing performance of the pad registration layer under hot and cold impact, and improves the reliability and hardness of the printed circuit board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503073000011
    Figure 2025503073000011
  • Figure 2025503073000012
    Figure 2025503073000012
  • Figure 2025503073000013
    Figure 2025503073000013
Patent Text Reader

Abstract

The present invention provides a photosensitive, thermosetting, developable resin composition capable of forming a solder resist layer having excellent printability, hardness, and thermal shock resistance, a dry film thereof, a cured product thereof, and a printed wiring board formed using them. The photosensitive, thermosetting, developable resin composition contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) a phosphate ester-based dispersant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, the (C) phosphate ester-based dispersant contains (C-1) a polymer having a phosphate ester structure in its main chain, the (E) inorganic filler contains talc and silica, the total amount of both the talc and silica is 50 to 180 parts by weight per 100 parts by weight of the (A) vinyl ester resin (solid content equivalent), and the proportion of talc is 20 to 80% by weight when the total amount of talc and silica is 100% by weight.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photosensitive, thermosetting, developable resin composition suitable for forming a solder resist agent for printed wiring boards, a dry film thereof, and a cured product thereof, and in particular to a photosensitive, thermosetting, developable resin composition capable of forming a solder resist layer having excellent printability, hardness, and cold / heat shock resistance, a dry film thereof, a cured product thereof, and a printed wiring board. [Background technology]

[0002] Currently, the solder resist agents used in some consumer printed wiring boards and most industrial printed wiring boards are alkaline development type solder resist agents that are exposed to ultraviolet light, developed to form a pattern, and then completely cured (mainly cured) by heat and / or light irradiation. Also, in semiconductor devices used in vehicles such as automobiles, trains, ships, and aircraft, there is a tendency for solder resist agents for highly reliable electronic materials to be used as solder resist agents for printed wiring boards.

[0003] However, general alkaline development type solder resists usually have poor crack resistance during thermal shock due to thermal expansion, etc., and poor reliability against changes in environmental temperature. Although cracks can be improved by selecting talc as a filler, printability and hardness are poor. In addition, talc and barium sulfate can be used as a filler to meet the requirements for thermal shock resistance of automotive solder resists, but printability and hardness are poor.

[0004] For example, the photocurable solder resist of Patent Document 1 uses silica, barium sulfate, and talc as fillers. The curable resin composition for solder resist layer of Patent Document 2 contains a carboxyl group-containing resin, a thermosetting component, a flame retardant, and an ion trapping agent, and the ion trapping agent is a mixture of a hydrotalcite-based ion trapping agent and an ion trapping agent other than hydrotalcite-based ion trapping agent, and aluminum hydroxide is used as an inorganic filler. The curable resin composition of Patent Document 3 is used as a permanent mask for printed wiring boards, and contains a resin containing an ethylenically unsaturated group and a carboxyl group in the molecule, a photopolymerization initiator, a photopolymerizable monomer, titanium oxide surface-treated with alumina, barium sulfate and / or talc, and an organic solvent. Patent Document 4 describes that the filler of the ultraviolet light-curable liquid photosensitive solder resist flexible ink is barium sulfate, talc, or silica. [Prior art documents] [Patent documents]

[0005] Patent document 1: CN114716868A Patent document 2: CN108137791A Patent document 3: CN101798432A Patent document 4: CN106380929A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to improve the printability of a solder resist, and the hardness of a dry film and a cured product formed therefrom, and to further improve the long-term reliability.

[0007] More specifically, an object of the present invention is to provide a photosensitive, thermosetting, developable resin composition capable of forming a solder resist layer having excellent printability and excellent hardness and resistance to thermal shock, a dry film thereof, a cured product thereof, and a printed wiring board. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and have found that the type of filler and additives have a significant effect on thermal shock resistance. The present invention has been completed by providing a photosensitive, thermosetting, developable resin composition that contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) a phosphate ester dispersant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, the (C) phosphate ester dispersant containing (C-1) a polymer having a phosphate ester structure in its main chain, the (E) inorganic filler containing talc and silica, the total amount of both talc and silica being 50 to 180 parts by weight relative to 100 parts by weight of the (A) vinyl ester resin (solid content equivalent), and the proportion of talc being 20 to 80% by weight when the total amount of talc and silica is 100% by weight. This photosensitive, thermosetting, developable resin composition can solve the above problems, and has completed the present invention.

[0009] That is, the photosensitive, thermosetting, developable resin composition of the present invention contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) a phosphate ester-based dispersant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, the (C) phosphate ester-based dispersant contains (C-1) a polymer having a phosphate ester structure in its main chain, the (E) inorganic filler contains talc and silica, the total amount of the talc and silica is 50 to 180 parts by weight per 100 parts by weight of the (A) vinyl ester resin (converted into solid content), and the proportion of talc is 20 to 80% by weight when the total amount of the talc and silica is 100% by weight.

[0010] It is also preferable to contain (F) other additives other than the (B) photopolymerization initiator and the (C) phosphate ester-based dispersant.

[0011] It is also preferable that the composition contains an epoxy resin (G).

[0012] It is also preferred that the solvent contains an organic solvent (H).

[0013] In addition, (C) the phosphate ester-based dispersant preferably further contains (C-2) a polymer having a phosphate ester structure in the side chain.

[0014] The dry film of the present invention is characterized in that it is obtained by applying the photosensitive, thermosetting and developable resin composition to a carrier film and drying it.

[0015] The cured product of the present invention is characterized in that it is obtained by applying the photosensitive / thermosetting / developable resin composition to copper and drying the composition to obtain a coating film, or by applying the photosensitive / thermosetting / developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on copper, and photocuring the resulting coating film.

[0016] The printed wiring board of the present invention is characterized in that it is obtained by applying the photosensitive, thermosetting, developable resin composition to a substrate and drying the composition to obtain a coating film, or by applying the photosensitive, thermosetting, developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on a substrate, photocuring the resulting coating film, and then thermally curing the resulting coating film.

[0017] The photosensitive, thermosetting, developable resin composition of the present invention is most characterized in that it contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) a phosphate ester-based dispersant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and, as the (C) phosphate ester-based dispersant, (C-1) a polymer having a phosphate ester structure in its main chain, and as the (E) inorganic filler, the (E) inorganic filler contains talc and silica.

[0018] Based on the characteristic configuration of the present invention, a polymer having a phosphate ester structure in the main chain is used, and talc and silica are used in place of barium sulfate, a conventional filler, with the blending ratio of the two being optimized, thereby effectively improving thermal shock resistance and improving printability and pencil hardness.

[0019] In response to this, by using talc and barium sulfate in combination as a filler, the requirement for thermal shock resistance of the solder resist can be satisfied, but the pencil hardness deteriorates (for example, Patent Document 1, etc.).

[0020] As described above, the inventors of the present invention conducted extensive research and found that talc as a filler had good flexibility and excellent crack resistance in a Temperature Cycle Test (hereinafter sometimes abbreviated as "TCT test"), but the surface hardness was significantly reduced. Furthermore, talc has a high oil absorption, which significantly deteriorates the printability of the ink. In contrast, silica has a high hardness and a low oil absorption. The above object of the present invention was achieved by using talc and silica in combination and optimizing the blending ratio of the two. Effect of the Invention

[0021] As described above, the present invention can provide a photosensitive, thermosetting, developable resin composition capable of forming a solder resist layer having excellent printability and excellent hardness and thermal shock resistance, a dry film thereof, a cured product thereof, and a printed wiring board. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a diagram showing a substrate for evaluating printability in the examples. [Diagram 2] FIG. 1 is an image showing cracks that occurred when evaluating thermal shock resistance in an embodiment. [Diagram 3] FIG. 13 is an image showing that no cracks were generated when evaluating thermal shock resistance in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Each of the components of the photosensitive, thermosetting, developable resin composition of the present invention will be described below. The photosensitive, thermosetting, developable resin composition of the present invention contains an inorganic filler (E). The inorganic filler (E) is characterized by containing talc and silica as essential components. Therefore, the inorganic filler (E) will be described first.

[0024] (E) Inorganic filler In the photosensitive, thermosetting and developable resin composition of the present invention, the talc used as the inorganic filler (E) is used to improve resistance to thermal shock, and the silica is used to improve printability.

[0025] The talc may be any one of magnesium carbonate, serpentine, silica / silica-alumina, and magnesium deposits, and may be any one of so-called silicate minerals, and may be in the form of a lump or fine powder. Surface treatment may or may not be performed. The oil absorption of the talc is suitably 20 to 100 ml / 100 g, preferably 30 to 90 ml / 100 g, and more preferably 40 to 80 ml / 100 g. The average particle size of the talc is suitably 1.0 to 20.0 μm, more preferably 2.0 to 10 μm, and even more preferably 3.0 to 8.0 μm.

[0026] Commercially available products include HD25 manufactured by Talc Mining Co., Ltd., Pingdu City, Shandong Province, and LMP-100 manufactured by Fuji Talc Industry Co., Ltd.

[0027] Silica may be either amorphous or crystalline, or a mixture thereof. Particularly preferred is amorphous (fused) silica. Surface treatment may or may not be performed. The oil absorption of silica is suitably 15 to 60 ml / 100 g, preferably 20 to 50 ml / 100 g, and more preferably 27 to 45 ml / 100 g. The average particle size of silica is suitably 0.1 to 10.0 μm, more preferably 1.0 to 8.0 μm, and even more preferably 2.0 to 6.0 μm.

[0028] Commercially available silica products include CS1002 and CS1002A manufactured by Jiangsu NOVORAY New Materials Co., Ltd., A-8 manufactured by Sibelco Co., Ltd., SE-40 manufactured by Tokuyama Co., Ltd., MSV25G manufactured by Tatsumori Co., Ltd., MLV-2114 manufactured by Tatsumori Co., Ltd., SO-E5 manufactured by ADMATECHS, and SO-E2 manufactured by ADMATECHS.

[0029] Regarding the blending ratio of talc and silica, when the total amount of both is 100% by weight, the lower limit of the talc ratio is appropriately 20% by weight or more, preferably 25% by weight or more, and more preferably 30% by weight or more. The upper limit of the talc ratio is appropriately 80% by weight or less, preferably 75% by weight or less, and more preferably 70% by weight or less. If the talc ratio is within the above range, the thermal shock resistance can be significantly improved. If it is less than 20% by weight, sufficient thermal shock resistance cannot be obtained, while if it exceeds 80% by weight, the printability and surface hardness of the solder resist film tend to decrease, although the thermal shock resistance is still excellent. This is presumably because talc has a high oil absorption amount, and if the amount used is too large, the printability of the ink is greatly affected. In contrast, silica has high hardness and low oil absorption, so by mixing the two in an appropriate ratio, it is possible to achieve both printability and pencil hardness (at least 4H, preferably 6H or higher), while also improving thermal shock resistance (able to withstand at least 1,000 cycles under thermal cycle conditions of -40°C to 160°C).

[0030] In addition, the total amount of both talc and silica is suitably 50 to 180 parts by weight, preferably 60 to 160 parts by weight, and more preferably 80 to 150 parts by weight, per 100 parts by weight of the vinyl ester resin (A) (solid content). Within the above range, it is possible to ensure that excellent thermal shock resistance can be obtained while achieving both printability and hardness.

[0031] From the viewpoint of further satisfying thermal shock resistance, pencil hardness and printability, it is preferable that the photosensitive, thermosetting and developable resin composition of the present invention does not contain barium sulfate.

[0032] (A) Vinyl ester resin

[0033] As the vinyl ester resin (A) in the photocurable thermosetting resin composition of the present invention, a known resin having an ethylenically unsaturated double bond in the molecule for imparting alkaline developability can be used. From the viewpoint of photocurability and development resistance, a carboxyl group-containing resin having an ethylenically unsaturated double bond in the molecule is particularly preferred. Moreover, the unsaturated double bond is more preferably derived from acrylic acid or methacrylic acid or a derivative thereof. As the vinyl ester resin (A), a resin using an epoxy resin as a starting material, a polyurethane resin having a urethane skeleton, a copolymer resin having a copolymer structure of an unsaturated carboxylic acid, or a resin using a phenol compound as a starting material is preferred. Specific examples of the vinyl ester resin (A) are shown below.

[0034] (1) A vinyl ester resin obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with one or more other compounds having an unsaturated double bond. (2) Photosensitive vinyl ester resins obtained by adding an ethylenically unsaturated group as a side group to a copolymer of an unsaturated carboxylic acid such as (meth)acrylic acid and one or more other compounds having an unsaturated double bond, using a compound having an epoxy group and an unsaturated double bond, such as glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, or (meth)acrylic acid chloride, etc.; (3) A photosensitive vinyl ester resin obtained by reacting a copolymer of a compound having an epoxy group and an unsaturated double bond, such as glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, with an unsaturated carboxylic acid, such as (meth)acrylic acid, and then reacting the resulting secondary hydroxyl group with a polybasic acid anhydride. (4) A photosensitive vinyl ester resin obtained by reacting a copolymer of an acid anhydride having an unsaturated double bond, such as maleic anhydride, and another compound having an unsaturated double bond with a compound having a hydroxyl group and an unsaturated double bond, such as 2-hydroxyethyl (meth)acrylate. (5) A vinyl ester resin obtained by reacting a polyfunctional epoxy compound with an unsaturated monocarboxylic acid and reacting the resulting hydroxyl group with a saturated or unsaturated polybasic acid anhydride. (6) A vinyl ester resin containing hydroxyl groups and carboxyl groups, which is obtained by reacting a hydroxyl group-containing polymer such as a polyvinyl alcohol derivative with a saturated or unsaturated polybasic acid anhydride, and then reacting the resulting carboxylic acid with a compound having an epoxy group and an unsaturated double bond in one molecule. (7) A vinyl ester resin obtained by reacting a reaction product of a polyfunctional epoxy compound, an unsaturated monocarboxylic acid, and a compound having in one molecule at least one alcoholic hydroxyl group and one reactive group other than the alcoholic hydroxyl group that reacts with an epoxy group, with a saturated or unsaturated polybasic acid anhydride. (8) A vinyl ester resin obtained by reacting a polyfunctional oxetane compound having at least two oxetane rings in one molecule with an unsaturated monocarboxylic acid, and reacting a primary hydroxyl group in the resulting modified oxetane resin with a saturated or unsaturated polybasic acid anhydride; and (9) A vinyl ester resin obtained by reacting a polyfunctional epoxy resin with an unsaturated monocarboxylic acid, followed by reaction with a polybasic acid anhydride to obtain a carboxyl group-containing resin, and then reacting the resulting resin with a compound having one oxirane ring and one or more ethylenically unsaturated groups in the molecule; (10) A vinyl ester resin obtained by reacting an unsaturated monocarboxylic acid with a bifunctional epoxy compound and then reacting the resulting hydroxyl group with a saturated or unsaturated polybasic acid anhydride.

[0035] Among these examples, the vinyl ester resins (2), (5), (7) and (9) are particularly preferred.

[0036] In this specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and mixtures thereof, and the same applies to other similar expressions hereinafter.

[0037] The vinyl ester resin (A) described above has a plurality of free carboxyl groups in the side chains of the main chain polymer, and therefore can be developed using a dilute aqueous alkali solution.

[0038] The acid value of the vinyl ester resin (A) is preferably in the range of 40 to 200 mgKOH / g, more preferably in the range of 45 to 120 mgKOH / g. If the acid value of the carboxyl group-containing resin is less than 40 mgKOH / g, alkaline development becomes difficult, while if it exceeds 200 mgKOH / g, the exposed area is dissolved in the developer, resulting in lines that are thinner than necessary, or in some cases, the exposed area and the unexposed area are dissolved and peeled off in the developer without distinction, making it difficult to draw a normal resist pattern, which is undesirable.

[0039] The weight-average molecular weight of the vinyl ester resin (A) varies depending on the resin skeleton, but is generally in the range of 2,000 to 150,000, and more preferably 5,000 to 100,000. If the weight-average molecular weight is less than 2,000, the tack-free performance after application to a substrate and drying may be poor, and the moisture resistance of the coating film after exposure may be poor, film loss may occur during development, and resolution may be significantly poor. On the other hand, if the weight-average molecular weight exceeds 150,000, the developability may be significantly poor and storage stability may be poor.

[0040] The amount of the vinyl ester resin (A) is desirably in the range of 20 to 60 mass % of the total composition in terms of solid content, and preferably 25 to 50 mass %. If the amount of the vinyl ester resin (A) is less than the above range, the strength of the coating film is reduced, which is not preferable. On the other hand, if the amount is more than the above range, the viscosity of the composition increases or the coatability is reduced, which is not preferable.

[0041] (B) Photopolymerization initiator The photopolymerization initiator used in the photosensitive, thermosetting, developable resin composition of the present invention is not particularly limited as long as it is a photopolymerization initiator generally used in photosensitive, thermosetting, developable resin compositions.

[0042] As the photopolymerization initiator, known ones can be used, including benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, and 4-(1-t-butyldioxy-1-methylethyl)acetophenone; acetophenones such as 2-methylanthraquinone, 2-amylanthraquinone, 2-t-butylanthraquinone, and 1-chloroanthraquinone; thioxanthones such as isopropyl thioxanthone, 2,4-dimethyl thioxanthone, 2,4-diisopropyl thioxanthone, and 2-chlorothioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenones such as benzophenone, 4-(1-t-butyldioxy-1-methylethyl)benzophenone and 3,3',4,4'-tetrakis(t-butyldioxycarbonyl)benzophenone; and oxoanthracene.

[0043] In addition, as the photopolymerization initiator, an oxime ester-based photopolymerization initiator having an oxime ester group, an alkylphenone-based photopolymerization initiator, an α-aminoacetophenone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a titanocene-based photopolymerization initiator, or the like can also be used.

[0044] Commercially available oxime ester photopolymerization initiators include Irgacure OXE01 and Irgacure OXE02 manufactured by BASF Japan, and N-1919 and NCI-831 manufactured by ADEKA CORPORATION. A photopolymerization initiator having two oxime ester groups in the molecule can be suitably used, and specifically, an oxime ester compound having a carbazole structure can be mentioned.

[0045] Commercially available alkylphenone photopolymerization initiators include α-hydroxyalkylphenones such as Omnirad 184, Omnirad 1173, Omnirad 2959, and Omnirad 127 manufactured by IGM Resins BV.

[0046] Specific examples of the α-aminoacetophenone-based photopolymerization initiator include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone, etc. Commercially available products include Omnirad 907, Omnirad 369, Omnirad 379, etc. manufactured by IGM Resins BV.

[0047] Specific examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, trifunctional or higher acylphosphine photopolymerization initiators, etc. The trifunctional or higher acylphosphine photopolymerization initiator may be a photopolymerization initiator having three or more acylphosphine oxide skeletons in one molecule, and can be represented by the following formula (I). JPEG2025503073000001.jpg28168In formula, A's are each independently a single bond, O, S or NR 3 represents G is a multifunctional compound (core) G-(AH) m+n where AH represents an alcohol group, an amino group, or a thiol group, m and n are both integers, and m+n is an integer between 3 and 10; m is an integer between 3 and 8; R1 and R2, independently of one another, each represent a C1-C aryl group that is uninterrupted or interrupted by one or more oxygen and / or sulfur atoms and / or one or more substituted or unsubstituted imino groups. 18 Alkyl groups, C6-C 12 Aryl groups and C5-C 12 or R1 and R2 are each independently a 5- to 6-membered heterocyclic group containing oxygen and / or nitrogen and / or sulfur atoms, which may be substituted with an aryl group, an alkyl group, an aryloxy group, an alkoxy group, a heteroatom and / or a heterocyclic group; R2 may be R1-(C=O)-; Y is O or S; R 3 is hydrogen or an alkyl group of C1 to C4.

[0048] Here, the photopolymerization initiator represented by formula (I) does not contain a photocurable ethylenically unsaturated group.

[0049] Preferably, in formula (I), m+n is an integer between 3 and 8, more preferably an integer between 3 and 6. For example, in formula I, m is an integer between 3 and 6, more preferably an integer between 3 and 5.

[0050] In formula (I), when A is oxygen, G-(AH) m+n is a polyhydroxy compound selected from the group consisting of monomeric polyols, oligomeric polyols, and polymeric polyols, and mixtures thereof. When A is sulfur, G-(AH) m+n is a polythiol compound. In formula (I), when A is nitrogen, G-(AH) m+n is a linear or branched polyamine. When A is a mixture of oxygen and / or nitrogen and / or sulfur, G-(AH) m+n is a compound containing different functional groups, for example a compound containing an amino group and a hydroxy group. Residue G- suitable for carrying out the present invention does not contain a photocurable ethylenically unsaturated group. When A is a single bond, G- is the G-(AH) exemplified above. m+nIt is a residue obtained by removing a hydroxy group and / or an amino group and / or a mercapto group from the above.

[0051] Preferably, G-(AH) m+n The number average molecular weight is 1,500 or less, more preferably 800 or less, and even more preferably 500 or less.

[0052] When n is not 0, the compound of formula (I) has alcoholic free groups and / or amino groups and / or mercapto groups.

[0053] Representative trifunctional or higher acylphosphine photopolymerization initiators included in formula (I) are shown in Table 1. Among them, PI-3, PI-4, PI-10, PI-11, PI-12, PI-14, and PI-17 are particularly preferred. By including such trifunctional or higher acylphosphine photopolymerization initiators, outgassing is suppressed, and a cured product with superior insulation reliability can be obtained.

[0054] [Table 1] JPEG2025503073000003.jpg226169JPEG2025503073000004.jpg227169JPEG2025503073000005.jpg183169 JPEG2025503073000006.jpg131169JPEG2025503073000007.jpg218169JPEG2025503073000008.jpg105169

[0055] Such tri- or higher functional acylphosphine photopolymerization initiators can be produced by the method described in Japanese Patent No. 6,599,446, for example.

[0056] As commercially available acylphosphine oxide photopolymerization initiators, Omnirad TPO manufactured by IGM Resins, Omnirad 819 and Omnipol TP manufactured by IGM Resins BV, and the like can be used.

[0057] Specific examples of the titanocene photopolymerization initiator include bis(cyclopentadienyl)(diphenyl)titanium(IV), bis(cyclopentadienyl)titanium(IV) dichloride, bis(cyclopentadienyl)-bis(2,3,4,5,6-pentafluorophenyl)titanium(IV), bis(cyclopentadienyl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium(IV), etc. Commercially available products include Omnirad 784 manufactured by IGM Resins BV.

[0058] The blending ratio of these photopolymerization initiators (B) is suitably 0.01 to 30 parts by weight, preferably 5 to 25 parts by weight, and more preferably 10 to 20 parts by weight, relative to 100 parts by weight (solid content equivalent) of the vinyl ester resin (A). If the amount of the photopolymerization initiator used is less than the above range, the photocurability of the composition deteriorates, whereas if it is too much, the properties as a solder resist agent deteriorate, which is not preferable.

[0059] (C) Phosphate ester dispersant The phosphate ester dispersant (C) used in the photosensitive, thermosetting, developable resin composition of the present invention refers to a compound or polymer having a phosphate ester structure represented by the following formula (II) in the main chain or side chain. JPEG2025503073000009.jpg36169

[0060] Among these, preferred is a polymer having a phosphate ester structure represented by formula (II) in its main chain or side chain, since it has good affinity with pigments, is used in solvent-free inks and solvent-based inks, and is suitable for stabilizing pigments in low-polarity systems (e.g., alkyd resins, acrylate resins, thermoplastic acrylic resins, and epoxy resins).

[0061] Furthermore, the present inventors have found that it is more preferable to mix silica with talc as a filler and use a polymer having a phosphate ester structure in the main chain (i.e., a polyphosphate ester polymer) and a polymer having a phosphate ester structure in the side chain as the phosphate ester dispersant (C) in order to improve thermal shock resistance while achieving both ink printability and surface hardness of the solder resist layer. In this case, the mixing ratio of the two is suitably 1:10 to 10:1 by weight, that is, (C-1) polymer having a phosphate ester structure in the main chain: (C-2) polymer having a phosphate ester structure in the side chain, preferably 1:5 to 5:1, more preferably 1:3 to 3:1, and even more preferably 1:2 to 2:1. In this way, a photosensitive, thermosetting, developable resin composition excellent in all of ink printability, surface hardness of the solder resist layer, and thermal shock resistance can be obtained.

[0062] The blending ratio of the (C) phosphate ester-based dispersant is suitably 0.01 to 20 parts by weight, preferably 0.1 to 15 parts by weight, and more preferably 1 to 10 parts by weight, per 100 parts by weight (solid content) of the (A) vinyl ester resin. If the amount of the (C) phosphate ester-based dispersant used is within the above range, it is possible to ensure that excellent thermal shock resistance can be obtained while achieving both printability and hardness. If the amount exceeds the above range, the properties as a solder resist agent are reduced, which is not preferable.

[0063] Commercially available phosphate ester dispersants include Tech-5011 (manufactured by Shanghai Taige Polymer Technology Co., Ltd.), BYK-102, BYK-103, BYK-106, BYK-110, BYK-111, BYK-118, BYK-142, and BYK-145 (manufactured by BYK-Chemie).

[0064] In this specification, the term "polymer" is a general term for homopolymers, copolymers and mixtures thereof, and the same applies to other similar expressions.

[0065] (D) Compounds having two or more ethylenically unsaturated groups in one molecule The compound (D) having two or more ethylenically unsaturated groups in one molecule used in the photosensitive, thermosetting and developable resin composition of the present invention is a compound that is photocured by irradiation with active energy rays to make the vinyl ester resin (A) insoluble in an alkaline aqueous solution or to help make the vinyl ester resin insoluble in an alkaline aqueous solution. Specific examples of such compounds include: Hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate, Monoacrylates or diacrylates of glycols such as ethylene glycol, methoxytetraethylene glycol, polyethylene glycol, and propylene glycol; Acrylamides such as N,N-dimethylacrylamide, N-methylolacrylamide, and N,N-dimethylaminopropylacrylamide; Aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; Polyols such as hexanediol, trimethylolpropane, pentaerythritol, dipentaerythritol, tris(2-hydroxyethyl) isocyanurate, etc., or polyhydric acrylates such as ethylene oxide adducts or propylene oxide adducts thereof, acrylates such as phenoxy acrylate, bisphenol A diacrylate, and ethylene oxide or propylene oxide adducts of these phenols; acrylates of glycidyl ethers such as glycerin diglycidyl ether, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and melamine acrylate, and at least one of the methacrylates corresponding to the above acrylates.

[0066] Further examples include epoxy acrylate resins obtained by reacting acrylic acid with a multifunctional epoxy resin such as a cresol novolac epoxy resin, and epoxy urethane acrylate compounds obtained by reacting a hydroxyl group of this epoxy acrylate resin with a half urethane compound of a hydroxyacrylate such as pentaerythritol triacrylate and a diisocyanate such as isophorone diisocyanate.

[0067] The amount of compound (D) having two or more ethylenically unsaturated groups in one molecule is preferably 5 to 100 parts by weight, more preferably 10 to 70 parts by weight, relative to 100 parts by weight of the vinyl ester resin (A) (based on solid content). If the amount is less than 5 parts by weight relative to 100 parts by weight of the vinyl ester resin (A), the photocurability of the resulting photosensitive, thermosetting, developable resin composition decreases, making it difficult to form a pattern by alkaline development after irradiation with active energy rays, which is not preferred. On the other hand, if the amount exceeds 100 parts by weight, the solubility in an alkaline aqueous solution decreases, making the cured coating film brittle, which is not preferred.

[0068] (F) Other additives As described above, the other additives in the present invention refer to additives other than the (B) photopolymerization initiator and the (C) phosphate ester-based dispersant.

[0069] Examples of such additives include known and commonly used colorants such as phthalocyanine blue, phthalocyanine green, iodine green, disazo yellow, crystal violet, titanium oxide, carbon black, and acid black; known and commonly used thermal polymerization inhibitors such as hydroquinone, hydroquinone monomethyl ether, tert-butylcatechol, pyrogallol, and phenothiazine; known and commonly used thickeners such as finely divided silica, organic bentonite, and montmorillonite; at least one of silicone-based, fluorine-based, and polymer-based defoamers and leveling agents; adhesion imparting agents such as imidazole-based, thiazole-based, and triazole-based agents; silane coupling agents; antioxidants such as phenol-based, phosphorus-based, and sulfur-based agents; and hindered amine-based light stabilizers.

[0070] The blending ratio of such additives (F) is suitably 0.01% by weight or more and 20% by weight or less of the total amount of the photosensitive, thermosetting, developable resin composition. If it is less than 0.01% by weight, the effect is not sufficiently obtained, while if it exceeds 20% by weight, the printability and hardness of the photosensitive, thermosetting, developable resin composition are unfavorably deteriorated.

[0071] (G) Epoxy resin In order to impart heat resistance, it is preferable to blend an epoxy resin having at least two epoxy groups in the molecule, that is, a multifunctional epoxy resin (G), in the photosensitive, thermosetting, developable resin composition used in the present invention.

[0072] Commercially available products include bisphenol A type epoxy resins such as jER828, jER834, jER1001, and jER1004 manufactured by Mitsubishi Chemical Corporation, EPICLON 840, 850, 850S, 1050, and 2055 manufactured by DIC Corporation, EPOTOTE YD-011, YD-013, YD-127, and YD-128 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., DER317, DER331, DER661, and DER664 manufactured by Dow Chemical Company, and Sumi-Epoxy ESA-011, ESA-014, ELA-115, and ELA-128 manufactured by Sumitomo Chemical Co., Ltd. (all trade names); jERYL903 manufactured by Mitsubishi Chemical Corporation, EPICLON 152, EPICLON 165, and NIPPON STEEL Chemical & Material Co., Ltd. Brominated epoxy resins such as EPOTOTE YDB-400 and YDB-500 manufactured by Dow Chemical Company, DER542 manufactured by Dow Chemical Company, and Sumi-Epoxy ESB-400 and ESB-700 manufactured by Sumitomo Chemical Co., Ltd. (all under the trade name); jER152 and jER154 manufactured by Mitsubishi Chemical Corporation, DEN431 and DEN438 manufactured by Dow Chemical Company, EPICLON N-730, EPICLON N-770, and EPICLON N-865 manufactured by DIC Corporation, EPOTOTE YDCN-701 and YDCN-704 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., EPPN-201, EOCN-1025, EOCN-1020, EOCN-104S, RE-306, and NC-3000 manufactured by Nippon Kayaku Co., Ltd., and Sumi-Epoxy manufactured by Sumitomo Chemical Co., Ltd. ESCN-195X, ESCN-220, NIPPON STEEL Chemical & Material Co., Ltd.Novolac type epoxy resins such as YDCN-700-2, YDCN-700-3, YDCN-700-5, YDCN-700-7, YDCN-700-10, YDCN-704, and YDCN-704A manufactured by Nippon Paint Chemical Co., Ltd., and EPICLON N-680, N-690, and N-695 (all trade names) manufactured by DIC Corporation; EPICLON 830 manufactured by DIC Corporation, jER807 manufactured by Mitsubishi Chemical Corporation, bisphenol F type epoxy resins such as EPOTOTE YDF-170, YDF-175, and YDF-2004 (all trade names) manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Hydrogenated bisphenol A type epoxy resins such as ST-2004, ST-2007, ST-3000 (trade names), and YX8034 manufactured by Mitsubishi Chemical Corporation; jER604 manufactured by Mitsubishi Chemical Corporation, and NIPPON STEEL Chemical & Material Co., Ltd.glycidylamine type epoxy resins such as EPOTOTE YH-434 manufactured by Sumitomo Chemical Co., Ltd. and Sumi-Epoxy ELM-120 manufactured by Sumitomo Chemical Co., Ltd. (all trade names); hydantoin type epoxy resins; alicyclic epoxy resins such as CELLOXIDE 2021P manufactured by Daicel Corporation (trade name); trihydroxyphenylmethane type epoxy resins such as YL-933 manufactured by Mitsubishi Chemical Corporation and EPPN-501 and EPPN-502 manufactured by Nippon Kayaku Co., Ltd. (all trade names); bixylenol type or biphenol type epoxy resins or mixtures thereof such as YL-6056, YX-4000, and YL-6121 manufactured by Mitsubishi Chemical Corporation (all trade names); EBPS-200, ADEKA Bisphenol S type epoxy resins such as EPX-30 manufactured by CORPORATION and EXA-1514 (trade name) manufactured by DIC Corporation; bisphenol A novolac type epoxy resins such as jER157S (trade name) manufactured by Mitsubishi Chemical Corporation; tetraphenylolethane type epoxy resins such as jERYL-931 (trade name) manufactured by Mitsubishi Chemical Corporation; heterocyclic epoxy resins such as TEPIC (trade name) manufactured by Nissan Chemical Industries, Ltd.; diglycidyl phthalate resins such as BRENMAR DGT manufactured by NOF Corporation; tetraglycidyl xylenoylethane resins such as ZX-1063 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.; Examples of epoxy resins that contain a naphthalene skeleton include ESN-190 and ESN-360 manufactured by Nippon Steel Chemical & Material Co., Ltd., HP-4032, EXA-4750, and EXA-4700 manufactured by DIC Corporation, glycidyl methacrylate copolymer epoxy resins such as CP-50S and CP-50M manufactured by NOF Corporation, and further include cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resins, and CTBN-modified epoxy resins (e.g., YR-102 and YR-450 manufactured by Nippon Steel Chemical & Material Co., Ltd.), but are not limited thereto. These epoxy resins may be used alone or in combination of two or more.

[0073] The content of the (G) epoxy resin is preferably 10 to 100 parts by weight, more preferably 20 to 90 parts by weight, and more preferably 30 to 80 parts by weight, per 100 parts by mass (solid content) of the (A) vinyl ester resin.

[0074] (H) Organic Solvent Regarding the organic solvent (H) used in the photosensitive, thermosetting, developable resin composition of the present invention, an organic solvent can be used for the purpose of synthesizing the carboxyl group-containing resin (A), preparing the composition, or adjusting the viscosity when applying the composition to a substrate or a carrier film.

[0075] Examples of such organic solvents include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. The organic solvents described above can be used alone or as a mixture of two or more kinds.

[0076] When the photosensitive, thermosetting and developable resin composition of the present invention is used in forming a solder resist agent for a printed wiring board, the composition is adjusted to a viscosity suitable for the coating method as necessary, and then applied to a printed wiring board on which a circuit has been formed in advance by a method such as screen printing, curtain coating, spray coating, or roll coating, and dried at a temperature of, for example, about 60 to 100°C as necessary to form a tack-free coating film. Next, the composition is selectively exposed to active light through a photomask on which a predetermined exposure pattern has been formed, and the unexposed area is developed with an alkaline aqueous solution to form a resist pattern. Furthermore, by heating to a temperature of, for example, about 140 to 180°C for thermal curing, the curing reaction of the epoxy resin and the polymerization of the vinyl ester resin are promoted, and various properties such as hardness, cold and heat shock resistance, heat resistance, solvent resistance, acid resistance, moisture absorption resistance, PCT resistance, adhesion, and electrical properties of the resulting resist film can be improved.

[0077] The alkaline aqueous solution used in the development may be an alkaline aqueous solution of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, etc. In addition, the irradiation light source used in the photocuring may be a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a semiconductor laser, a solid state laser, a xenon lamp, a metal halide lamp, etc. The photosensitive, thermosetting, developable resin composition of the present invention can be used in the form of a photocurable dry film obtained by applying the photosensitive, thermosetting, developable resin composition to a carrier film in advance and drying it, other than the method of directly applying the composition to a substrate in liquid form. The case where the photosensitive, thermosetting, developable resin composition of the present invention is used as a photocurable dry film is shown below. The photocurable dry film has a structure in which a carrier film, a resin layer, and a peelable cover film used as required are laminated in this order. The resin layer is a layer obtained by applying the photosensitive, thermosetting, developable resin composition of the present invention to a carrier film or a cover film and drying it. After forming a resin layer on a carrier film, a cover film is laminated thereon, or a resin layer is formed on a cover film, and this laminate is laminated on a carrier film to obtain a dry film. The carrier film is a thermoplastic film such as a polyester film having a thickness of 2 to 150 μm. The resin layer is formed by uniformly applying a photosensitive, thermosetting, developable resin composition to a thickness of 10 to 150 μm on the carrier film or cover film using a blade coater, lip coater, comma coater, film coater, or the like, and then drying the composition. The cover film may be a polyethylene film, a polypropylene film, or the like, but it is preferable that the adhesive strength with the resin layer is smaller than that of the carrier film. The cured product of the present invention is obtained by applying a photosensitive, thermosetting, developable resin composition to copper and drying the composition to obtain a coating film, or by applying the photosensitive, thermosetting, developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on copper, and photocuring the resulting coating film. To prepare a cured product on a printed wiring board having a copper circuit using a photocurable dry film, the cover film is peeled off, the resin layer and the substrate on which the circuit is formed are superimposed, and the substrates are laminated together using a laminator or the like to form a resin layer on the substrate on which the circuit is formed. The formed resin layer is exposed to light, developed, and cured by heating in the same manner as described above to form a cured product. The carrier film may be peeled off either before or after exposure. The photosensitive, thermosetting, developable resin composition is suitably used for forming a cured film on a printed wiring board. The cured film is preferably a permanent insulating film, and more preferably a solder resist.

[0078] The present invention will be described in more detail with reference to examples and comparative examples, but the scope of the present invention and its embodiments are not limited thereto. "Parts" and "%" in the examples and comparative examples are by weight unless otherwise specified. The property values ​​of the composition of this example are tested by the method described below.

[0079] Synthesis Example In a four-neck flask equipped with a stirrer and a reflux condenser, 214 parts of cresol novolac epoxy resin EPICLON N-695 (DIC, epoxy equivalent = 214) were added, and 103 parts of diethylene glycol monoethyl ether acetate and 103 parts of a petroleum-based hydrocarbon solvent (Japan Energy Corporation, product name: Cactus Fines SF-01) were added and dissolved by heating. Next, 0.1 parts of hydroquinone as a polymerization inhibitor and 2.0 parts of triphenylphosphine as a reaction catalyst were added. This mixture was heated to 95-105°C, 72 parts of acrylic acid were slowly dropped, and the reaction was carried out for 16 hours. The obtained reaction product was cooled to 80-90°C, 91.2 parts of tetrahydrophthalic anhydride were added, the reaction was carried out for 8 hours, and the product was taken out after cooling. The carboxyl group-containing vinyl ester resin thus obtained had a non-volatile content of 65% and an acid value of the solid content of 87.5 mgKOH / g.

[0080] The vinyl ester resin solution (varnish) of the above Synthesis Example was used, and the components and ratios (parts by weight) shown in Table 1 were blended and premixed with a stirrer, and then kneaded with a three-roll mill to prepare a photosensitive, thermosetting and developable resin composition. Furthermore, the printability, pencil hardness and thermal shock resistance were evaluated by the following methods.

[0081] [Table 1]

[0082] A Cresol novolac type epoxy modified acrylic resin (solid content 65%) prepared in the above synthesis example F Pigment: Phthalocyanine Green, Pigment A manufactured by DIC Corporation Defoamer: KS-66, manufactured by Shin-Etsu Chemical Co., Ltd. C-1 Phosphate ester dispersant: BYK-110, polymerized phosphate ester, polyphosphate ester polymer, manufactured by BYK-Chemie, solid content 52% by mass, oil absorption 63 ml / 100 g C-2 Phosphate ester dispersant: BYK-142, a compound of 2-ethylhexyl acrylate and (ethylenediamine-ethyleneimine polymer) with polyethylene polypropylene glycol monobutyl ether phosphate, manufactured by BYK-Chemie, solid content 60% by mass, oil absorption 29ml / 100g B Photoinitiator: Omnirad 369 E, manufactured by IGM E Talc: LMP-100, manufactured by FUJI TALC INDUSTRIAL Silica: A-8 Sibelco Barium sulfate: B-30, manufactured by Sakai Chemical Industry Co., Ltd. H Solvent: PGMEA, Propylene Glycol Monomethyl Ether Acetate CC G Epoxy resin: N-770-75EA, manufactured by DIC Corporation, novolac type multifunctional epoxy resin, solid content 75% by mass D Compound having two or more ethylenically unsaturated groups in one molecule: MT-3501G, manufactured by Zhangjiagang Dongya Di-Chi Biochemical Co., Ltd.

[0083] Performance evaluation

[0084] (1) Printability A substrate having a copper opening pattern of φ400μm and pitch 600μm was coated with the photosensitive, thermosetting and developable resin compositions of the Examples and Comparative Examples by screen printing over the entire surface, and the substrate was left to stand at room temperature for 30 minutes, and then dried at 80°C for 30 minutes in a hot air circulation drying oven to prepare a substrate for printability evaluation. The substrate for printability evaluation was observed using a 100x optical microscope to evaluate the rate of air bubble generation in the copper openings (see Figure 1). The evaluation criteria are shown below. Good: The rate of air bubbles is less than 40%. △: The bubble generation rate is 40% or more but less than 50%. ×: The rate of bubble generation is 50% or more.

[0085] (2) Pencil hardness The photosensitive, thermosetting, developable resin compositions of the above-mentioned Examples and Comparative Examples were applied by screen printing to the entire surface of a copper foil-clad laminate substrate that had been pretreated by polishing, dried at 80°C for 30 minutes, and cooled to room temperature to form a resin layer with a thickness of 40 μm. The resin layer was exposed to 400 mJ / cm using an exposure device equipped with a high-pressure mercury lamp. 2 The pattern was exposed to light at 400 nm and developed for 50 seconds using a 1% by weight aqueous solution of sodium carbonate at 30° C. under a spray pressure of 0.15 MPa. The pencil hardness of the resin surface after thermal curing of the resulting resin coating was measured according to JIS K 5600-5-4. The evaluation criteria are as follows: 〇: Pencil hardness is 6H or higher. △: Pencil hardness is 4H or more but less than 6H. ×: Pencil hardness is less than 4H.

[0086] (3) Thermal shock resistance The photosensitive, thermosetting, developable resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80°C for 30 minutes. After cooling to room temperature, the coating was exposed to 400 mJ / cm using an exposure device equipped with a high-pressure mercury lamp. 2 Then, the resist was developed with a 1 wt% aqueous sodium carbonate solution at a pressure of 0.2 MPa and a liquid temperature of 30°C for 60 seconds, and then cured in a hot air circulation drying oven at 150°C for 60 minutes. The cumulative exposure in the UV transfer oven was 2000 mJ / cm 2 By irradiating ultraviolet light under the above conditions, 17 evaluation boards with right-angled resist patterns were fabricated for crack resistance during thermal cycles. The evaluation boards fabricated as described above were placed in a temperature cycler that performs thermal cycles at -40°C to 160°C, and a thermal shock cycle test (TCT test) was performed by setting different cycle numbers. Next, the appearance was observed for each number of cycles, and the maximum number of cycles at which cracks did not occur was recorded, and the evaluation criteria are shown below (see Figures 2 and 3 for images of when cracks occurred and did not occur). ◯: No cracks were observed even after 1000 cycles. ×: Cracks occurred in less than 1000 cycles.

[0087] As can be seen from the above, by adjusting the compositions of Examples 1 to 6, a photosensitive, thermosetting, developable resin composition excellent in all of printability, pencil hardness, and thermal shock resistance can be obtained. In contrast, in Comparative Example 1, only barium sulfate was used as the filler, so both printability and pencil hardness were excellent, but the thermal shock resistance was extremely low. In Comparative Example 2, only talc was used as the filler, so the thermal shock resistance was excellent, but the printability and pencil hardness were significantly deteriorated. In Comparative Example 3, a combination of talc and barium sulfate was used, and in Comparative Example 4, a combination of silica and barium sulfate was used, but in neither case was it possible to achieve excellent thermal shock resistance while simultaneously achieving printability and pencil hardness. In Comparative Examples 5 to 8, talc and silica were used in combination, the compounding ratio of the two was outside the range of the present application in Comparative Example 5, and the total amount of both was increased to 200 parts by weight in Comparative Examples 6 to 8. As a result, the thermal shock resistance did not meet the requirements for any of the thermal shock resistances, and in Comparative Examples 6 and 8, there were adverse effects on the printability and pencil hardness. In Comparative Example 9, based on Example 2, the same amount of phosphate ester-based dispersant BYK-145 was used, and as a result, printability and pencil hardness were significantly deteriorated.

Claims

1. (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) a phosphate ester-based dispersant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, The (C) phosphate ester-based dispersant contains (C-1) a polymer having a phosphate ester structure in its main chain, The photosensitive, thermosetting and developable resin composition is characterized in that the (E) inorganic filler contains talc and silica, the total amount of the talc and silica is 50 to 180 parts by weight per 100 parts by weight of the (A) vinyl ester resin (converted into solid content), and the proportion of talc is 20 to 80% by weight when the total amount of the talc and silica is taken as 100% by weight.

2. 2. The photosensitive, thermosetting and developable resin composition according to claim 1, further comprising (F) another additive other than the (B) photopolymerization initiator and the (C) phosphate ester-based dispersant.

3. 2. The photosensitive, thermosetting and developable resin composition according to claim 1, further comprising an epoxy resin (G).

4. 2. The photosensitive, thermosetting and developable resin composition according to claim 1, further comprising (H) an organic solvent.

5. The photosensitive, thermosetting, developable resin composition according to any one of claims 1 to 4, wherein the (C) phosphate ester-based dispersant further contains (C-2) a polymer having a phosphate ester structure in a side chain.

6. A photocurable dry film obtained by applying the photosensitive, thermosetting, developable resin composition according to any one of claims 1 to 5 to a carrier film and drying the applied composition.

7. A coating film obtained by applying the photosensitive, thermosetting, and developable resin composition according to any one of claims 1 to 5 to copper and drying the composition, or a cured product obtained by applying the photosensitive, thermosetting, and developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on copper, and photocuring the resulting coating film.

8. A printed wiring board comprising: a coating film obtained by applying the photosensitive, thermosetting, developable resin composition according to any one of claims 1 to 5 to a substrate and drying the composition; or a cured product obtained by applying the photosensitive, thermosetting, developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on a substrate, photocuring the coating film, and then thermally curing the resulting cured product.

Citation Information

Patent Citations

  • Photosensitive resin composition, two-liquid type photosensitive resin composition, dry film and printed wiring board

    JP2019174787A